Kemanjuran Teknik Homeroom dalam Bingkai Bimbingan Kelompok untuk Meningkatkan Konsep Diri Siswa Sekolah Menengah Kejuruan - Hidayati, Bella Aulia (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Self-concept is a crucial aspect of student development, particularly in vocational education settings where identity and confidence impact learning outcomes. Enhancing self-concept through guidance and counseling services is essential for student growth. Objective: This study aims to determine the self-concept of class X Hospitality 2 students after being given group guidance services using the homeroom technique. Method: This is a follow-through research in guidance and counseling involving 36 students from class X Hospitality 2 at SMK Negeri 3 Cimahi. Data were collected using a self-concept measurement tool based on the Tennessee Self Concept Scale (TSCS) developed by William H. Fitss (1971) and modified by Julia Raymond Lorenz (2002), consisting of 70 items. Group guidance was implemented in two cycles: three meetings in cycle I and two meetings in cycle II, with six students participating in the intervention. The Wilcoxon test was used for data analysis. Result: The Wilcoxon test showed a Z value of 0.028, with a significance level of 5%, indicating Z count > Z table (0.028 < 0.0028). In addition, the mean post-test score (211) was higher than the pre-test score (167), suggesting an improvement in students' self-concept after the homeroom technique group guidance. Conclusion: The homeroom technique in group guidance services effectively improves the self-concept of class X Hospitality 2 students. Contribution: This study contributes to the field of guidance and counseling by providing evidence of the effectiveness of the homeroom technique in enhancing self-concept among vocational high school students and can be used as a reference for future interventions and research.